2011
DOI: 10.1002/etc.665
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of perchloroethylene residues in dry‐cleaned fabrics

Abstract: We have used a novel gas chromatography/mass spectrometry (GC/MS)-based approach to quantify perchloroethylene (PCE) residues in dry-cleaned fabrics. Residual PCE was extracted from fabric samples with methanol and concentration was calculated by the gas chromatographic peak area, standardized using PCE calibration data. Extracts examined were from samples of 100% wool, polyester, cotton, or silk, which were dry cleaned from one to six times in seven different Northern Virginia dry-cleaning establishments. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…There is recognition that adsorption and desorption of indoor-relevant gases on fabrics for tobacco smoke products [30][31][32] and pesticides 21 can influence exposure. Several studies have shown that dry-cleaning solvents [33][34][35][36] and moth repellants 37 can sorb to clothing and subsequently desorb, increasing indoor concentrations. Specialty fabrics have been developed that sorb or react with chemical warfare agents or pesticides to protect the wearer.…”
Section: Resultsmentioning
confidence: 99%
“…There is recognition that adsorption and desorption of indoor-relevant gases on fabrics for tobacco smoke products [30][31][32] and pesticides 21 can influence exposure. Several studies have shown that dry-cleaning solvents [33][34][35][36] and moth repellants 37 can sorb to clothing and subsequently desorb, increasing indoor concentrations. Specialty fabrics have been developed that sorb or react with chemical warfare agents or pesticides to protect the wearer.…”
Section: Resultsmentioning
confidence: 99%
“…This solvent has been widely used for dry cleaning clothes, and exposures occur when visiting dry cleaning establishments, and storing dry cleaned clothes at home, whether or not clothes are wrapped in plastic (Sherlach et al, 2011), as noted in Table 1. PERC exposures were higher among employed participants.…”
Section: Resultsmentioning
confidence: 99%
“…Models that predict the impact of clothing on dermal uptake have been developed but require knowledge of the sorptive capacity of the clothing and its exposure history prior to being worn. Accumulation of organic compounds with clothing fabrics has been quantified using laboratory chambers, inferred from dynamic uptake experiments and from fabrics exposed to air in an office . The latter method best assesses the accumulation under real‐world environmental conditions.…”
Section: Introductionmentioning
confidence: 99%